Analysis of the Potential for Installing a Solar Power Plant on a BNI Bank Rooftop in the City of Balikpapan Permai - Vicky Andria Kusuma; Sena Sukmananda Suprapto; Aji Akbar Firdaus; Jenrychk Marcelino Tandi Karrang (International Journal of Reconfigurable and Embedded Systems (IJRES), 2023)
The installation of a solar energy generation system is being carried out to increase the use of renewable energy. This research is on the availability of many solar pandies behind the equator and requires banks. The Solar Power Plant (SPP) design results in the Bank Negara Indonesia (BNI) Balikpapan Permai bank building have shown good potential to be implemented even in changing climatic conditions. The SPP system has a total power higher than the total power consumption in the BNI bank building, with a power consumption of 33 kW. In comparison, for the SPP system in November, the power was 50,78 kW, and the power generated in December was 5,696 kW. This means that the BNI office receives an electricity surplus of 12,696 kW - 17,78 kW, with a total power of 9,8 kW from solar modules used.